PENGEMBANGAN PLUGIN UNTUK RESERVASI HOTEL PADA MESIN CMS WORDPRESS - Sukarsa, I Made; Yartono, Kadek (Majalah Ilmiah Teknologi Elektro; Vol 9, No 2 (2010): (July - December) Majalah Ilmiah Teknologi Elektro, 2012)
Website is a very important medium for promotion in the field of business. The existence of the website allows the transaction process is done online. Online transactions has provided various facilities both in the consumer and business owner. One is for the hotel reservation online (via website) which allows the reservation process can be done without having to go to your hotel destination. Development of a website from scratch requires a cost, time and great energy. WordPress is a CMS (Content Management System) that can be used to build a website that can be done quickly and cost-efficient. WordPress has the components (plugins) that can be added and subtracted as you wish. Based on a search on internet (2010) has not been available free plugin to handle the reservation process. Therefore it is necessary to develop a plugin to meet those needs. This plugin can handle the addition of master data for a hotel room, reservation by a travel agent or without a travel agent (individual or group), blocking list that displays the data-filled room or empty, the process of checking in and checking out, as well as additional data and making travel agent report.